A heat-resistant copper-based powder metallurgy friction material and preparation method thereof
By using chromium powder and ultrafine copper powder in copper-based powder metallurgy friction materials to improve the interface combination between graphite and copper, combined with precise feeding and anhydrous ethanol solution treatment, the interface binding strength of copper-based powder metallurgy friction materials in the prior art is solved. The poor problem achieves high thermal conductivity and heat resistance of the material, simplifies the process flow and reduces costs.
Patent Information
- Application Number
- CN202211669314.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-24
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2042-12-24
AI Technical Summary
During the sintering process, the bonding strength between graphite and copper is poor, resulting in unstable tribological and thermal conductivity, and the preparation process is complex and costly, making it difficult to meet the performance requirements of high-speed train braking systems.
The transition layer of compound is used for chromium powder as the interface modification component and graphite is used to enhance the interface combination with ultrafine copper powder. The process flow is simplified by precise feeding and ladder feeding methods, and the adsorption of metal elements is enhanced by using anhydrous ethanol solution. During sintering, it is carried out. Hydrogen gas protects the atmosphere and improves the thermal conductivity and heat resistance of the material.
It significantly improves the thermal conductivity and heat resistance of powder metallurgical friction materials, simplifies the preparation process, reduces production costs, and ensures the stability and safety of material performance.
Smart Images

Figure CN116000282B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of friction materials, and in particular relates to a heat-resistant copper-based powder metallurgy friction material and a preparation method thereof. Background Art
[0002] Braking technology, as the core technology of high-speed trains, is related to the safety and stability of train operations. In the emergency braking state of high-speed trains, huge kinetic energy will be generated instantly and a large amount of friction heat will accumulate, with the temperature approaching 1000℃. The high temperature leads to the accumulation of heat, which makes the braking system performance decrease or even fail. The selection and preparation of brake materials directly affect the quality of safe braking performance. With the development of materials science, alloy composite materials with more advantages have been developed and put into use one after another.
[0003] Copper-based powder metallurgy friction materials have become the most reliable and widely used high-speed train brake friction materials due to their excellent mechanical properties, thermal conductivity and wear resistance. Graphite has become the first choice for the lubricating component of copper-based powder metallurgy friction materials due to its excellent thermal conductivity and low acquisition cost. However, due to its defects such as immiscible with the copper matrix and poor interface bonding during the sintering process, the tribological properties and thermal conductivity of copper-based powder metallurgy friction materials are unstable. There have been some related studies on copper-based powder metallurgy friction materials. For example, in "A Preparation Method for Copper-Based Powder Metallurgy Friction Material Containing Mixed Graphite" (application number 202110278542.5), the raw material powder is mixed, cold pressed and sintered to form a friction material. It has the defect of poor interface bonding strength between graphite and copper due to one-time mixing. In "A copper-zinc alloy composite material and its preparation method" (application number 201810031498.6), a copper-zinc composite material is prepared by acid treatment, sensitization treatment, activation treatment, copper or zinc plating on the surface of graphite or foam carbon, and alloying treatment of the copper-zinc plating layer. The alloy material made by this process realizes the alloying of the graphite surface by chemically plating metal on graphite, but the preparation process has high requirements for equipment, the process flow is cumbersome and complicated, and the process waste liquid is seriously polluted. In "A powder metallurgy friction material for railway passenger cars and its preparation method" (application number 201910620516.9), copper powder, iron powder, tin powder, chromium powder alloy powder, nickel powder, manganese powder, molybdenum alloy powder and ferrophosphorus powder are mechanically alloyed, and then the remaining components and binder are added to mix, and then cold pressing, degumming treatment and pressureless high-temperature sintering are performed to prepare powder metallurgy friction materials. This method simultaneously mechanically alloys multiple metal elements to form a multi-component complex interface system, which leads to the obstruction of friction heat conduction and poor thermal conductivity. Based on the above, it can be seen that the current method of improving the interface between copper and graphite in powder metallurgy friction materials is mainly through graphite surface alloying, but the existing method has high requirements on equipment and complex process flow. It is greatly affected by various process parameters in the actual production process and it is difficult to meet the requirements of friction performance and thermal conductivity.
[0004] Therefore, it is of positive significance to develop a preparation method based on ensuring material properties, with a simple process flow and low process cost. Summary of the invention
[0005] The purpose of the present invention is to provide a heat-resistant copper-based powder metallurgy friction material, which has excellent thermal conductivity, a simple preparation method and a low production cost.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] A heat-resistant copper-based powder metallurgy friction material, wherein the components in the friction material are calculated in mass percentage as follows:
[0008] Copper coated iron powder 70-80%;
[0009] Molybdenum disulfide 3-5%;
[0010] Alumina 2-4%;
[0011] Silicon dioxide 0.7-0.9%;
[0012] Zinc stearate 0.3-0.5%;
[0013] The interface bonding component prepared from graphite and chromium powder as raw materials is 13-16%; the mass percentage of the graphite in the friction material is 5-12%, and the mass percentage of the chromium powder in the friction material is 3-4%.
[0014] The interface bonding enhancer is 5-8%; the interface bonding enhancer is ultrafine copper powder.
[0015] As a more preferred technical solution of the present invention, the components in the friction material are calculated in mass percentage as follows:
[0016] Copper-clad iron powder 71%;
[0017] Ultrafine copper powder 6%;
[0018] Graphite 10%;
[0019] Chromium powder 3.7%;
[0020] Molybdenum disulfide 5%;
[0021] Alumina 3%;
[0022] Silicon dioxide 0.8%;
[0023] Zinc stearate 0.5%.
[0024] Another object of the present invention is to provide a method for preparing the friction material comprising the following steps:
[0025] S1. Weigh the raw materials according to the above mass percentage;
[0026] S2. Accurately feed the raw materials and feed them in stages;
[0027] S21, putting the weighed chromium powder and graphite into a ball mill and mixing them for 50 to 150 minutes at a rotation speed of 60 to 180 r / min to obtain a mixed powder 1;
[0028] S22, adding ultrafine copper powder to mixed powder 1, putting into a ball mill and mixing for 50 to 150 minutes at a rotation speed of 60 to 180 r / min to obtain mixed powder 2;
[0029] S23, adding anhydrous ethanol solution to the mixed powder 2 and letting it stand for 30 to 60 minutes to obtain a mixed powder 3, wherein the anhydrous ethanol content is 0.3%
[0030] S24, vacuum drying the mixed powder 3 at 40-60° C. for 100-120 min, and obtaining the mixed powder 4 after the anhydrous ethanol solution is completely evaporated;
[0031] S25, adding copper-coated iron powder, molybdenum disulfide, aluminum oxide, silicon dioxide, and zinc stearate to the mixed powder four in order, putting into a ball mill and mixing for 10 to 20 minutes at a rotation speed of 120 r / min to obtain a mixed powder five;
[0032] S3, hot pressing the mixed powder into a green body, the pressing pressure is 500-600 MPa, the holding time is 50-60 seconds, and demolding is performed to obtain a sample block;
[0033] S4. The sample is pressurized and sintered to obtain a heat-resistant powder metallurgy friction material. Hydrogen is introduced as a protective atmosphere during the sintering process. The sintering pressure is 1 to 2 MPa and the sintering temperature is 800 to 1000°C.
[0034] As a more optimal technical solution of the present invention: the copper-clad iron powder has a purity of 99%, a particle size of 35-45 μm, and a copper mass percentage of 35% and an iron mass percentage of 65% in the copper-clad iron powder.
[0035] As a more optimal technical solution of the present invention: the ultrafine copper powder has a purity of 99% and a particle size of 6 to 7 μm.
[0036] As a more optimal technical solution of the present invention: the graphite is natural flake graphite with a particle size of 180 to 250 μm.
[0037] As a more optimal technical solution of the present invention: the chromium powder is an irregular powder with a purity of 99% and a particle size of 6 to 7 μm.
[0038] As a more optimal technical solution of the present invention: the molybdenum disulfide is a flaky powder with a purity of 98% and a particle size of 30 to 50 μm.
[0039] As a more optimal technical solution of the present invention: the silicon dioxide and aluminum oxide are both irregular powders with a purity of 95% and a particle size of 50 to 100 μm.
[0040] As a more optimal technical solution of the present invention: in the step S21, chromium powder and graphite are put into a ball mill and mixed for 120 minutes at a rotation speed of 130 r / min to obtain mixed powder 1.
[0041] As a more optimal technical solution of the present invention: in the step S22, the ultrafine copper powder is added to the mixed powder 1 obtained in the first stage of mixing, and the mixed powder 2 is obtained by mixing in a ball mill for 120 minutes at a rotation speed of 130 r / min.
[0042] As a more optimal technical solution of the present invention: the mixed powder three obtained in step S24 is placed in a vacuum drying oven for drying for 110 minutes at a temperature of 45° C., and after the anhydrous ethanol solution is completely evaporated, a mixed powder four is obtained.
[0043] As a more optimal technical solution of the present invention: add the remaining components in step S25 to the mixed powder four obtained in the second stage of mixing in order, mix in a ball mill for 15 minutes at a rotation speed of 120r / min to obtain mixed powder five.
[0044] The beneficial effects are as follows:
[0045] 1. The present invention provides a friction material having an interface bonding component, wherein chromium powder is used as an interface modification component. The chromium powder element has a high affinity for graphite and can form a compound transition layer with graphite after sintering. Ultrafine copper powder is used as a material component and is attached to the outer layer of the chromium powder to further enhance the bonding between the graphite and the chromium powder. At the same time, the local high temperature generated by the exothermic reaction during the sintering process further modifies the interface, thereby improving the interface bonding state of graphite and copper, improving the thermal conductivity of the powder metallurgy friction material, and enhancing its heat resistance.
[0046] 2. The friction material preparation process of the present invention adopts a method of precise feeding and step-feeding. The raw materials are mixed in batches and then fed in sequence, so that the chromium powder is better adsorbed on the graphite surface, and raw materials are saved. The reaction process is more controllable. Compared with the traditional graphite surface coated with metal chromium powder, the preparation process is simplified and the production cost is reduced.
[0047] 3. The friction material preparation process of the present invention uses anhydrous ethanol solution to reduce costs. In addition, anhydrous ethanol as a polar molecule solvent further enhances the adsorption of metal elements. Also, since the anhydrous ethanol solution is volatile and does not react with various raw materials, other impurities will not be introduced after vacuum drying. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 1 is the XRD diffraction pattern of mixed powder 1 after the first stage of step-by-step feeding in Example 1.
[0049] Figure 2 It is a schematic structural diagram of the heat-resistant copper-based powder metallurgy friction material of the present invention. DETAILED DESCRIPTION
[0050] The present invention is further defined in the following examples. Based on the following description and these examples, those skilled in the art can ascertain the essential characteristics of the present invention and, without departing from the essence and scope of the present invention, can make various changes and modifications to the present invention to adapt it to various uses and conditions.
[0051] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial channels.
[0052] Example 1
[0053] A heat-resistant copper-based powder metallurgy friction material, the preparation method of which comprises the following steps:
[0054] Step 1. Weigh the required raw materials according to the types and mass percentages of the raw materials; the components and their weight ratios are 71% copper-clad iron powder, 6% ultrafine copper powder, 10% graphite, 3.7% chromium powder, 5% molybdenum disulfide, 3% aluminum oxide, 0.8% silicon dioxide and 0.5% zinc stearate.
[0055] Step 2: Use precise feeding and step-by-step feeding. The specific feeding sequence and operation process are as follows:
[0056] A. Precision feeding stage 1: put the chromium powder and graphite weighed in step 1 into a ball mill, mix for 100 minutes at a speed of 140 r / min to obtain mixed powder 1;
[0057] B. Precision feeding stage 2: Add ultrafine copper powder to the mixed powder 1 obtained in the first stage of mixing, put it into a ball mill and mix it for 100 minutes at a speed of 120r / min to obtain mixed powder 2;
[0058] C. Adsorption consolidation stage: add an appropriate amount of anhydrous ethanol solution to the mixed powder 2 and let it stand for 45 minutes to obtain mixed powder 3;
[0059] D. Vacuum drying: The obtained mixed powder 3 was placed in a vacuum drying oven for drying for 100 min at a temperature of 50°C. After the anhydrous ethanol solution was completely evaporated, the mixed powder 4 was obtained.
[0060] E. Step feeding stage: add the remaining components to the mixed powder 4 obtained in the second stage of mixing according to the designed sequence, mix in a ball mill for 10 minutes at a speed of 120 r / min to obtain mixed powder 5;
[0061] Step 3: Suppression:
[0062] The mixed powder 5 obtained in step 2 is placed in the mold cavity of a hot press, and hot-pressed into a green body at a pressing pressure of 550 MPa and a holding time of 60 seconds, and then demolded and taken out to obtain a sample block;
[0063] Step 4: Pressure sintering:
[0064] The sample formed in step three is placed in a sintering furnace for pressure sintering. Hydrogen is introduced as a protective atmosphere during the sintering process. The sintering pressure is 1.8 MPa, the sintering temperature is 950°C, and the sintering time is 1.5 h. A heat-resistant powder metallurgy friction material is obtained.
[0065] Example 2
[0066] The difference between this embodiment and embodiment 1 is that:
[0067] By raw material type and mass percentage: copper-clad iron powder 74%, ultrafine copper powder 5%, graphite 10%, chromium powder 3.2%, molybdenum disulfide 3%, aluminum oxide 3.7%, silicon dioxide 0.8%, zinc stearate 0.3%.
[0068] Example 3
[0069] The difference between this embodiment and embodiment 1 is that:
[0070] By raw material type and mass percentage: copper-clad iron powder 70%, ultrafine copper powder 7%, graphite 11%, chromium powder 4%, molybdenum disulfide 4%, aluminum oxide 2.7%, silicon dioxide 0.9%, zinc stearate 0.4%.
[0071] Example 4
[0072] The difference between this embodiment and embodiment 1 is that:
[0073] By raw material type and mass percentage: copper-clad iron powder 80%, ultrafine copper powder 5%, graphite 5%, chromium powder 4%, molybdenum disulfide 3%, aluminum oxide 2%, silicon dioxide 0.7%, zinc stearate 0.3%.
[0074] Example 5
[0075] The difference between this embodiment and embodiment 1 is that:
[0076] By raw material type and mass percentage: copper-clad iron powder 70%, ultrafine copper powder 8%, graphite 10%, chromium powder 3.7%, molybdenum disulfide 4%, aluminum oxide 3%, silicon dioxide 0.8%, zinc stearate 0.5%.
[0077] Example 6
[0078] The difference between this embodiment and embodiment 1 is that:
[0079] A. Precision feeding, first stage: put the chromium powder and graphite weighed in step 1 into a ball mill, mix for 120 min at a speed of 130 r / min, and obtain mixed powder 1.
[0080] Example 7
[0081] The difference between this embodiment and embodiment 1 is that:
[0082] B. Precision feeding stage 2: Add ultrafine copper powder to the mixed powder 1 obtained in the first stage of mixing, put it into a ball mill and mix it for 120 minutes at a speed of 130 r / min to obtain mixed powder 2.
[0083] Example 8
[0084] The difference between this embodiment and embodiment 1 is that:
[0085] C. Adsorption consolidation stage: Add an appropriate amount of anhydrous ethanol solution to mixed powder 2 and let stand for 40 minutes to obtain mixed powder 3.
[0086] Example 9
[0087] The difference between this embodiment and embodiment 1 is that:
[0088] D. Vacuum drying: The obtained mixed powder 3 is placed in a vacuum drying oven for drying for 110 min at a temperature of 45° C., and after the anhydrous ethanol solution is completely evaporated, a mixed powder 4 is obtained.
[0089] Example 10
[0090] The difference between this embodiment and embodiment 1 is that:
[0091] E. Step feeding stage: add the remaining components to the mixed powder 4 obtained in the second mixing stage in order, mix in a ball mill for 15 minutes at a rotation speed of 120 r / min to obtain mixed powder 5.
[0092] Embodiment 11
[0093] The difference between this embodiment and embodiment 1 is that:
[0094] The pressed sample was placed in a sintering furnace for pressure sintering. Hydrogen was introduced as a protective atmosphere during the sintering process. The sintering pressure was 1.8 MPa, the sintering temperature was 900°C, and the sintering time was 1.5 h. The heat-resistant powder metallurgy friction material was obtained.
[0095] Comparative Example 1
[0096] Firstly, copper-clad iron powder, ultrafine copper powder, graphite, chromium powder, molybdenum disulfide, aluminum oxide, silicon dioxide and zinc stearate are added into a mixer in a specified proportion and mixed for 210 minutes. The mixed powder is hot-pressed into a green body with a pressing pressure of 550 MPa and a holding time of 55 s. The sample is demolded and taken out to obtain a sample. The sample is pressure-sintered to obtain a heat-resistant powder metallurgy friction material. Hydrogen is introduced as a protective atmosphere during the sintering process. The sintering pressure is 2 MPa and the sintering temperature is 900°C.
[0097] Comparative Example 2
[0098] Firstly, copper-clad iron powder, molybdenum disulfide, aluminum oxide, silicon dioxide, zinc stearate and graphite are added into a mixer in a specified proportion and mixed for 150 minutes to obtain a mixed powder one. Ultrafine copper powder and chromium powder are then added to the mixed powder one. The obtained mixed powder is hot-pressed into a green body at a pressing pressure of 550 MPa and a holding time of 55 s. The sample is demolded and taken out to obtain a sample block. The sample block is pressure-sintered to obtain a heat-resistant powder metallurgy friction material. During the sintering process, hydrogen is introduced as a protective atmosphere. The sintering pressure is 2 MPa and the sintering temperature is 900°C.
[0099] Comparative Example 3
[0100] Firstly, copper-clad iron powder, ultrafine copper powder, molybdenum disulfide, aluminum oxide, silicon dioxide, zinc stearate and graphite are added into a mixer in a specified proportion and mixed for 130 minutes to obtain a mixed powder one. Chromium powder is then added to the mixed powder one. The obtained mixed powder is hot-pressed into a green body at a pressing pressure of 550 MPa and a holding time of 55 s. The sample is demolded and taken out to obtain a sample. The sample is pressure-sintered to obtain a heat-resistant powder metallurgy friction material. During the sintering process, hydrogen is introduced as a protective atmosphere. The sintering pressure is 2 MPa and the sintering temperature is 900°C.
[0101] Comparative Example 4
[0102] Firstly, copper-clad iron powder, chromium powder, molybdenum disulfide, aluminum oxide, silicon dioxide, zinc stearate and graphite are added into a mixer in a specified proportion and mixed for 140 minutes to obtain a mixed powder 1. Ultrafine copper powder is then added to the mixed powder 1. The obtained mixed powder is hot-pressed into a green body at a pressing pressure of 550 MPa and a holding time of 55 s. The sample is demolded and taken out to obtain a sample. The sample is pressure-sintered to obtain a heat-resistant powder metallurgy friction material. During the sintering process, hydrogen is introduced as a protective atmosphere. The sintering pressure is 2 MPa and the sintering temperature is 900°C.
[0103] The mass percentages of the raw materials in the comparative example are 71% copper-clad iron powder, 6% ultrafine copper powder, 10% graphite, 3.7% chromium powder, 5% molybdenum disulfide, 3% aluminum oxide, 0.8% silicon dioxide and 0.5% zinc stearate.
[0104] The friction materials prepared in the examples and comparative examples were tested for thermal conductivity, and the results are shown in Table 1.
[0105] Table 1
[0106] Example <![CDATA[Thermal conductivity (W·m -1 ·K -1 )]]> 1 608 2 599 3 587 4 604 5 598 6 594 7 603 8 591 9 602 10 594 11 592 Comparative Example <![CDATA[Thermal conductivity (W·m -1 ·K -1 )]]> 1 398 2 399 3 405 4 412
[0107] The mixed powder in Example 1 was subjected to XRD detection, and it was shown that the combination of graphite and chromium produced two substances, CrC and Cr2C, which enhanced the interface bonding. The diffraction spectrum of Example 1 is as follows: Figure 1 The mixed powders in the comparative example were subjected to XRD detection, and no CrC and Cr2C were found, which is the reason why the thermal conductivity of the comparative example in Table 1 is low.
[0108] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A heat-resistant copper-based powder metallurgy friction material, characterized in that: The components in the friction material are calculated in mass percentage as follows: Copper coated iron powder 70-80%; Molybdenum disulfide 3-5%; Alumina 2-4%; Silicon dioxide 0.7-0.9%; Zinc stearate 0.3-0.5%; The interface bonding component prepared from graphite and chromium powder as raw materials is 8-16%, the mass percentage of the graphite in the friction material is 5-12%, and the mass percentage of the chromium powder in the friction material is 3-4%; 5-8% of an interface bonding enhancer, wherein the interface bonding enhancer is ultrafine copper powder; The friction material preparation method comprises the following steps: S1. Weigh the raw materials according to the mass percentage; S2. Accurately feed the raw materials and feed them in stages; S21, putting the weighed chromium powder and graphite into a ball mill and mixing them for 50 to 150 minutes at a rotation speed of 60 to 180 r / min to obtain a mixed powder 1; S22, adding ultrafine copper powder to mixed powder 1, putting into a ball mill and mixing for 50 to 150 minutes at a rotation speed of 60 to 180 r / min to obtain mixed powder 2; S23, adding anhydrous ethanol solution to the mixed powder 2 and letting it stand for 30 to 60 minutes to obtain a mixed powder 3; S24, vacuum drying the mixed powder 3 at 40-60° C. for 100-120 min, and obtaining the mixed powder 4 after the anhydrous ethanol solution is completely evaporated; S25, adding copper-coated iron powder, molybdenum disulfide, aluminum oxide, silicon dioxide, and zinc stearate to the mixed powder four in order, putting into a ball mill and mixing for 10 to 20 minutes at a rotation speed of 120 r / min to obtain a mixed powder five; S3, hot pressing the mixed powder into a green body, the pressing pressure is 500-600 MPa, the holding time is 50-60 seconds, and demolding is performed to obtain a sample block; S4. The sample is pressurized and sintered to obtain a heat-resistant powder metallurgy friction material. Hydrogen is introduced as a protective atmosphere during the sintering process. The sintering pressure is 1 to 2 MPa and the sintering temperature is 800 to 1000°C.
2. The heat-resistant copper-based powder metallurgy friction material according to claim 1, characterized in that: The particle size of the copper-clad iron powder is 35-45 μm, the mass percentage of copper in the copper-clad iron powder is 35%, and the rest is iron.
3. The heat-resistant copper-based powder metallurgy friction material according to claim 1, characterized in that: The particle size of the ultrafine copper powder is 6-7 μm.
4. The heat-resistant copper-based powder metallurgy friction material according to claim 1, characterized in that: The graphite is natural flake graphite with a particle size of 180 to 250 μm.
5. The heat-resistant copper-based powder metallurgy friction material according to claim 1, characterized in that: The chromium powder is irregular powder with a particle size of 6 to 7 μm.
6. The heat-resistant copper-based powder metallurgy friction material according to claim 1, characterized in that: The molybdenum disulfide is in the form of flaky powder with a particle size of 30 to 50 μm.
7. The heat-resistant copper-based powder metallurgy friction material according to claim 1, characterized in that: The silicon dioxide and aluminum oxide are both irregular powders with a particle size of 50 to 100 μm.
8. The heat-resistant copper-based powder metallurgy friction material according to claim 1, characterized in that: In the step S21, chromium powder and graphite are put into a ball mill and mixed for 120 minutes at a rotation speed of 130 r / min to obtain mixed powder 1.
9. The heat-resistant copper-based powder metallurgy friction material according to claim 1, characterized in that: In the step S22, the ultrafine copper powder is added to the mixed powder 1 obtained in the first stage of mixing, and the mixed powder 1 is put into a ball mill for mixing for 120 minutes at a rotation speed of 130 r / min to obtain the mixed powder 2.
10. The heat-resistant copper-based powder metallurgy friction material according to claim 1, characterized in that: In step S24, the obtained mixed powder three is placed in a vacuum drying oven for drying for 110 minutes at a temperature of 45° C., and after the anhydrous ethanol solution is completely evaporated, a mixed powder four is obtained.
